2010
DOI: 10.1303/jjaez.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Annual Number of Generations of the Rice Bug, Leptocorisa chinensis Dallas (Hemiptera: Alydidae), Using the Development of Gonads and Formation of Endocuticle Layers after Adult Emergence

Abstract: Abstract:To clarify the timing of the appearance of overwintered and diapausing adults of the rice bug, Leptocorisa chinensis, under natural condition, we adopted two criteria, the developmental stages of gonads and the number of endocuticle layers in the cuticle of the hind-leg femur. Development of gonads after emergence was promoted in adults reared under a long-day photoperiodic condition, but suppressed under a short-day condition. The deposition rate of endocuticle layers was not influenced by the photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…In the milkweed bug, it is reported that flight is depressed and feeding activity frequent during the teneral period, in which the cuticle layer hardens after adult molt and reaches full growth at 9-10 days (Dingle 1965;Caldwell and Rankin 1974). In L. chinensis, the teneral period is 7 days after adult molt (Matsuki et al 2010). It is possible that L. chinensis may also suppress locomotion activity and spend time feeding during this 7 days of the teneral stage, which corresponds to the duration of the ''settling mode''.…”
Section: Discussionmentioning
confidence: 99%
“…In the milkweed bug, it is reported that flight is depressed and feeding activity frequent during the teneral period, in which the cuticle layer hardens after adult molt and reaches full growth at 9-10 days (Dingle 1965;Caldwell and Rankin 1974). In L. chinensis, the teneral period is 7 days after adult molt (Matsuki et al 2010). It is possible that L. chinensis may also suppress locomotion activity and spend time feeding during this 7 days of the teneral stage, which corresponds to the duration of the ''settling mode''.…”
Section: Discussionmentioning
confidence: 99%